High-Resolution Melting Analysis for Genotyping of Canine Parvovirus 2 Strains in Indian Context: Challenges and Insights - Nair, Aswathy; Paramasivam, Raja; Parthiban, Manoharan; Gopal, Sathish; Chandraseka, Muniswamy; Vivekanandan, Vinitha (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study focuses on the detection and differentiation of Canine Parvovirus 2 (CPV-2) strains in India using High Resolution Melt (HRM) curve analysis. CPV-2 is a highly contagious virus causing acute haemorrhagic enteritis and myocarditis in dogs, with a high mortality rate. A total of 25 faecal swab samples were collected from suspected CPV cases, out of which 20 tested positive for CPV using PCR targeting the VP2 gene. These positive samples were further analyzed using HRM, which predicted them to belong to the CPV2a strain based on their melting temperature (71.4° or less). Two CPV2a positive samples were sequenced, they were found to belong to CPV2b strains, indicating a discrepancy between HRM prediction and sequencing results. Single nucleotide polymorphic variations were observed at positions 4062 and 4064, confirming their classification as CPV2b strains.Phylogenetic analysis of VP2 capsid gene showed that these field samples were closely related to CPV2c strains, suggesting potential genetic diversity among circulating CPV strains in India. The study highlights the importance of developing geographically specific CPV strain primers for accurate detection and differentiation using HRM. It raises concerns about potential co-infections or the emergence of new strains, indicated by varying melting temperatures in field samples.
Keywords: Canine parvovirus (CPV); sequencing; PCR-HRM; canine faecal swabs; Strain differentiation